Development of Picture Story Book Learning Media to Increase Elementary School Students' Interest in Reading English - Marhamah, Marhamah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This study aimed to develop a picture storybook learning media to increase interest in reading English for elementary school students in grade 5 SDN Pekanbaru Riau. This study uses research and development methods (Research and Development). This research will produce learning tools in the form of learning media, which will be tested for validity and practicality. The steps in developing picture storybooks for learning to read follow the 4-D model (Define, Design, Development, Disseminate). The test subjects in this research and development were class V students at SDN Pekanbaru Riau. This research and development trial was conducted on a small group of 5 students. The type of data taken in this research is qualitative and quantitative data. At the product validation stage, the data obtained is qualitative in the form of responses and comments from student interviews after using the media, as well as input, criticism, and suggestions from validators and teachers in improving picture storybooks. Furthermore, quantitative data is obtained from statements in providing assessments of media products during validation by media, material, and language validators, and teacher response questionnaire assessments. After the data is obtained, the next step is to analyze the data. The data that will be obtained in this research is quantitative and qualitative. Quantitative data was obtained from media, material and language validation sheets, and teacher response questionnaires. Furthermore, qualitative data was obtained from student interviews and input from validators and teachers. Responses, suggestions, and validator input are considered and analyzed to improve the product. The results of this research are the result of expert validation of picture storybook learning media material of 81%. They are included in the 80-100% interval so that they are included in the high category and are very suitable for use. The results of this study are the results of expert validation of picture storybook learning media material as much as 81 % and belonging to the 80-100% interval so that it is included in the high category and is very feasible to use. The results of the validation from media experts on the development of picture storybook learning media to increase interest in reading for grade 5 SDN students are in the high category with the eligibility of 78% from 3 aspects. The validated aspects included the suitability of the presentation with the demands of student-centered learning, the way of presentation, readability, and communicativeness. The suitability of the presentation with the demands of student-centered learning has a feasibility of 68%, which is in the high category.